The Influence of Compensation, Academic Supervision, Pedagogic Competency, and Work Motivation on the Performance of Business and Management Teachers of Vocational Schools - Habibi, Beni; Joko Raharjo, Tri; Rifa’i, Achmad; Rusdarti, Rusdarti (The Journal of Educational Development, 2018)
The success of education management is determined by the teachers’ readiness in preparing the process of education through teaching and learning instructions. At present, the problem is how the teachers’ performance is associated more with the quality of education. The performance of qualified teachers is demonstrated by the attitudes of the teachers who are capable and ready to play their professional role in the two major environments, school, and society. This study examines the teachers’ performance with various factors that influence it. This is a quantitative research study. The population was all business and management teachers of vocational schools (SMK) in Tegal City amounting to 202 teachers. The number of samples was 130 teachers. The data were collected through questionnaires that have been tested for validity and reliability. The data were then analyzed employing the path analysis with SPPS software version 19 and Sobel test to assess the mediation variables. The results show that (1) the influence of compensation, academic supervision, and academic competence on the teachers’ work motivation was proven to be accepted; (2) the effect of compensation and academic supervision on the teachers’ performance was proven to be accepted; (3) the influence of work motivation on the teachers’ performance was proven to be accepted. Work motivation is a mediating variable. The results show a positive and significant influence. It is suggested that teachers continue to improve their work motivation and understand the academic supervision when performing tasks with various determining factors. Pedagogic competence needs to be continuously improved as a place to develop the teachers' performance.